Prevalence of persistent proteinuria in stable HIV/AIDS patients and its association with HIV nephropathy - Maria Alina Gomes de Mattos Cavalcante (Brazilian Journal of Infectious Diseases)
Human immunodeficiency virus (HIV)-related glomerular disease is a cause of end-stage renal disease, though there is no recent data from Brazil concerning this syndrome. Persistent proteinuria (PPt) is the main marker for glomerular disease, especially levels above 1.5 g. We examined the prevalence of and associated risk factors for PPt, along with the prevalence of HIV-associated nephropathy (HIVAN) among AIDS patients. We interviewed 411 patients who were attended at the HIV/AIDS section of the Clinical Hospital of the Federal University of Pernambuco (Brazil) from January through June 2004. PPt was defined as a positive urine dipstick exam on at least two occasions. The analyzed risk factors were: black race, a low CD4 lymphocyte count (<200 cells/mm³), an HIV RNA level of >100,000 copis/mL and patients on highly-active antiretroviral therapy (HAART). The patients were classified according to urineary protein/creatinine ratio (Up/Uc) < 1.0, 1.0-3.0 and > 3.0. Patients with Up/Uc >3.0 were submitted to renal biopsy. Among the 411 HIV/AIDS patients, the mean age was 37 years, 70% were male, 37.5% were black, the mean CD4 count was 363 cells/mm³ (± 95), the mean RNA HIV count was 44,475 copies/mL (± 40,369), and 92% were on HAART. The prevalence of PPt was 5.6% (95% CI = 3.6 to 8.3%), and it was significantly associated with a low CD4 lymphocyte count (p<0.048). HIVAN was found in just one patient, and two patients improved after HAART.